The Role of Local Leaders in Environmental Concerns in Master Plans: An Empirical Study of China's Eighty Large Municipalities. (September 2018) - Zhang, Lei; Tochen, Rachel M.; Hibbard, Michael; Tang, Zhenghong
Limited research has explored the reasons behind the level of environmental concerns in master plans in China, where serious environmental degradation has caught the world's attention and the planning regime is significantly different from those based on representative democracy. Analyzing eighty master plans of China's large municipalities, we find that the education and age of local leaders have a significant effect on environmental concerns in master plans, while their work experience and state mandate do not. We conclude that that well-educated local leaders and a more collaborative planning approach could deal more efficiently with environmental problems in China.